Enhancing Student’s Reading Ability Trough Literal Translation Strategy Using Arabic-Indonesian Electronic Dictionary at Al-Hidayah Islamic Institute - Ilma, Maulia Humaini; Maulana, Asep; Huda, Mokhammad Miftakhul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The Al-Hidayah Islamic boarding school has many activities, including the sorogan yellow kitab. The weakness of the translation process among students in teaching the book makes the researcher want to improve to it. Therefore, the researcher compared whether literal translation was effective for students’ reading skill or not. This research approach quantitative, while this type of research is experiment quantitative. The population in this research were 78 students of Islamic boarding school Al-Hidayah, while the sample taken from class eleven was 16 students. The techniques used quantitative descriptive statistics, validity test, normality test, paired t test and N-Gain score. In this test, the average N-Gain value was (0.5986) or (59.8595%). Based on the result mentioned, the literal translation strategy in the Arabic-Indonesian electronic dictionary was effective in improving the reading skill of students at Al-Hidayah Islamic boarding school for academic year 2023/2024. Meanwhile for the normality value of the Sig. (2-tailed) pretest of 1.155 and posttest of 0.448 its greater than 0,05. Hypothesis test of literal translation strategy with Arabic-Indonesian electronic dictionary to improve reading skills of Islamic boarding school Al-Hidayah students that H1 is accepted and H0 is rejected. Results paired t-test Sig (2-tailed) is (0.001) less than (0.05). Therefore, the literal translation strategy in the Arabis-Indonesian electronic dictionary is effective in improving the reading skill of students at Al-Hidayah Islamic boarding school for the academic year 2023/2024.